Unveiling antidiabetic and antioxidant activities of biogenically synthesized red fluorescent graphene quantum dots using Bauhinia variegata L. leaves - Pooja Kadyan; Jaya Saini; Parul Singh; Ponnusamy Thillai Arasu; Sudhir Kumar Kataria (Discover Sustainability)
Abstract In recent years, the utilization of green synthesis routes for the production of nanomaterials has garnered considerable attention owing to their eco-friendly nature and multifaceted applications. Present study presents the phyto-mediated synthesis of red fluorescent graphene quantum dots using the leaves of Bauhinia variegata as a sustainable precursor. The synthesized GQDs were characterized through various analytical techniques i.e. UV–visible spectroscopy, FT-IR, fluorescence spectrophotometry, XRD, DLS and TEM to confirm their structural and optical properties. The bio-functional properties of the GQDs were explored, focusing on their antidiabetic and antioxidant activities. The antidiabetic potential of the GQDs was evaluated by measuring their inhibitory effects on α-amylase and α-glucosidase enzymes, which are key to glucose metabolism. Furthermore, antioxidant activity was assessed using DPPH⋅ scavenging assays, demonstrating the free radical neutralizing ability of the GQDs. The study found that the synthesized graphene quantum dots (GQDs) were more effective than the leaf extract in antioxidant and enzyme inhibition activities. The GQDs showed lower IC50 values for DPPH⋅ radical scavenging (51.232 ± 6.478 µg/mL), α-amylase inhibition (135.309 ± 4.970 µg/mL), and α-glucosidase inhibition (147.551 ± 5.549 µg/mL) compared to the leaf extract, which showed higher IC50 values of 71.157 ± 6.134 µg/mL, 157.660 ± 7.463 µg/mL, 152.455 ± 4.630 µg/mL respectively. The findings highlight the multifunctionality of Bauhinia derived GQDs as promising materials for biomedical and environmental applications, offering eco-friendly alternatives for antidiabetic treatments and antioxidant therapy.